Simulation of transition from Townsend mode to glow discharge mode in a helium dielectric barrier discharge at atmospheric pressure - 李雪辰 牛东莹 许龙飞 贾鹏英 常媛媛 (Chinese physics B, 2012)
The dielectric barrier discharge characteristics in helium at atmospheric pressure are simulated based on a one- dimensional fluid model. Under some discharge conditions, the results show that one discharge pulse per half voltage cycle usually appears when the amplitude of external voltage is low, while a glow-like discharge occurs at high voltage. For the one discharge pulse per half voltage cycle, the maximum of electron density appears near the anode at the beginning of the discharge, which corresponds to a Townsend discharge mode. The maxima of the electron density and the intensity of electric field appear in the vicinity of the cathode when the discharge current increases to some extent, which indicates the formation of a cathode-fall region. Therefore, the discharge has a transition from the Townsend mode to the glow discharge mode during one discharge pulse, which is consistent with previous experimental results.